2016
DOI: 10.1080/15384047.2016.1235654
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin reactivates hMOF in gastric cancer cells and induces cell growth inhibition

Abstract: Capsaicin (CAP) is the major pungent component of chili pepper and is being evaluated for use against numerous types of tumors. Although CAP is indicated to target multiple signaling pathways, exact mechanisms of how it disturb cancer cell metablism remain obscure. Recent studies revealed Sirtuin 1 (SIRT1) serves as a potential target of CAP in cancer cells, indicating a direct regulation of cancer cell histone acetylation by capsaicin. The present study evaluated the effect of CAP on gastric cancer (GC) cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The members of this family are responsible for post-translationally modifying histones and nonhistone proteins [31,32]. Few previous studies have examined the association between capsaicin and SIRT1, and even fewer have assessed their role in growth regulation [33,34,35]. We previously reported that tNOX knockdown in T24 cells reversed cancer phenotypes in association with downregulation of SIRT1 and cyclin D1, even though the details of the underlying mechanism remained unclear [19].…”
Section: Discussionmentioning
confidence: 99%
“…The members of this family are responsible for post-translationally modifying histones and nonhistone proteins [31,32]. Few previous studies have examined the association between capsaicin and SIRT1, and even fewer have assessed their role in growth regulation [33,34,35]. We previously reported that tNOX knockdown in T24 cells reversed cancer phenotypes in association with downregulation of SIRT1 and cyclin D1, even though the details of the underlying mechanism remained unclear [19].…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin targets some signaling pathways involved in carcinogenesis and tumor invasion, but its global impact is not entirely known, despite the observation that it may disturb cancer cell metabolism [ 28 ] implying some anti-neoplastic biologic effects. However, in most cases, this action on cancer cells’ metabolism seems to be independent of TRPV1 [ 29 ].…”
Section: Capsaicin In Gastrointestinal Cancermentioning
confidence: 99%
“…A recent study by Wang et al showed a new epigenetic action of capsaicin capable of regulating cell growth in gastric cancer [ 28 ]. The authors showed that capsaicin promotes the activity of histone acetyltransferase hMOF inducing a positive feedback loop ending in cell cycle arrest and apoptosis in SGC-7901 and MGC-803 gastric cancer cells.…”
Section: Capsaicin In Gastrointestinal Cancermentioning
confidence: 99%
“…[11][12][13] Unlike the above findings, more studies have provided evidence that CAP is a potential anti-tumour compound in a wide variety of cancer types, including breast cancer, lung cancer, gastric cancer, liver cancer, prostate cancer and bladder cancer, and so on. [14][15][16][17][18][19][20] There may be more complex molecular biology events behind these contradictory views of CAP. In addition, when combined with certain chemotherapeutic drugs such as 5-Fu, cisplatin, and pirarubicin, CAP can enhance the anti-tumour activity of these drugs, [21][22][23] suggesting that CAP has broad application prospects and may be used as a potential chemopreventive and therapeutic drug for cancer.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…23 CAP also induces cell growth inhibition by reactivating hMOF and associated H4K16ac. 15 In the study of apoptosis, CAP induces apoptosis in human gastric cancer cells AGS in the presence of p53 47 or by modulating MAPK signalling pathway. 48 which is associated with the late apoptotic extracellular passive release of HMGB1, HSP70 and HSP90, the second line of hallmarks required for ICD.…”
Section: Stomach Cancermentioning
confidence: 99%